Benefits of side‐by‐side deployment of 6‐mm covered self‐expandable metal stents for hilar malignant biliary obstructions. (1st August 2016) - Yoshida, Tsukasa; Hara, Kazuo; Imaoka, Hiroshi; Hijioka, Susumu; Mizuno, Nobumasa; Ishihara, Makoto; Tanaka, Tsutomu; Tajika, Masahiro; Niwa, Yasumasa; Yamao, Kenji
Abstract: Background: The best way to perform endoscopic stenting for hilar malignant biliary obstruction (HMBO) is under discussion. Recently, a 6‐mm covered self‐expandable metal stent (CSEMS) has become available. In this article, the results of side‐by‐side (SBS) 6‐mm CSEMS deployment for HMBO are reported. Methods: A total of 22 patients, 32 procedures of SBS 6‐mm CSEMS [16 fully covered (FCSEMS), 16 partially covered (PCSEMS)] deployment for HMBO, were prospectively enrolled from November 2011 to June 2015 and retrospectively analyzed. Technical and clinical success rates, stent patency period, complications, and re‐intervention success rates were analyzed. Results: The overall/FCSEMS/PCSEMS technical and clinical success rates were 96.9%/93.8%/100% and 93.5%/100%/87.5%, respectively. The mean stent patency period was 95/113/68 days. Early and late complication rates were 3.1%/0%/6.3% and 6.3%/12.5%/0%, respectively. Stent exchange was attempted in 12 procedures, and the stent exchange success rate was 83.3%/100%/75%. Conclusions: This is the first report of SBS 6‐mm CSEMS deployment for HMBO. This procedure has high technical and clinical success rates and the advantages of ease of performance and a high success rate of re‐intervention. Outcomes appear better with FCSEMS than with PCSEMS deployment. Since stent patency is still controversial, large‐sample studies are needed. Abstract : Highlight Yoshida and colleagues report that side‐by‐side deployment of 6‐mm covered self‐expandable metal stents (SEMS) was efficient for hilar malignant biliary obstruction. The fully covered type (FCSEMS) had a good stent patency period. All occluded FCSEMS could be removed, and revision of the FCSEMS was achieved in six of seven cases.